Heat shock factor 1 induces crystallin-αB to protect against cisplatin nephrotoxicity - Lou, Qiang (Am J Physiol Renal Physiol, 2016)
Cisplatin, a wildly used chemotherapy drug, induces nephrotoxicity that is characterized by renal tubular cell apoptosis. In response to toxicity, tubular cells can activate cytoprotective mechanisms, such as the heat shock response. However, the role and regulation of the heat shock response in cisplatin-induced nephrotoxicity remain largely unclear. In the present study, we demonstrated the induction of heat shock factor (Hsf)1 and the small heat shock protein crystallin-αB (CryAB) during cisplatin nephrotoxicity in mice. Consistently, cisplatin induced Hsf1 and CryAB in a cultured renal proximal tubular cells (RPTCs). RPTCs underwent apoptosis during cisplatin treatment, which was increased when Hsf1 was knocked down. Transfection or restoration of Hsf1 into Hsf1 knockdown cells suppressed cisplatin-induced apoptosis, further supporting a cytoprotective role of Hsf1 and its associated heat shock response. Moreover, Hsf1 knockdown increased Bax translocation to mitochondria and cytochrome c release into the cytosol. In RPTCs, Hsf1 knockdown led to a specific downregulation of CryAB. Transfection of CryAB into Hsf1 knockdown cells diminished their sensitivity to cisplatin-induced apoptosis, suggesting that CryAB may be a key mediator of the cytoprotective effect of Hsf1. Taken together, these results demonstrate a heat shock response in cisplatin nephrotoxicity that is mediated by Hsf1 and CryAB to protect tubular cells against apoptosis.